Valoración de los activos intangibles en las empresas Agroindustriales de la Provincia de San Martín (periodo-2013). - Chinguel Ortiz, Julián (2015)
The objective of this research is to describe the valuation of intangible assets in agribusiness firms in the province of San Martín 2013. Inductive method was used because general conclusions are obtained from particular premises, through the observation of facts for registration; classification and study of these; inductive derivation of the facts and let’s get to a generalization; and calibration. Intangible assets that are present in the agribusiness companies that are part of our study are the most basic, this mainly due to company size (micro) and lack of knowledge to identify them, the importance assigned to intangible assets present in the companies is allocated according to the economic and commercial benefits that give them. Al Cataloging the main intangible assets present in agribusiness enterprises sector in the province of San Martin. Under investigation found that these if they recognized the most basic assets that may be present in a company, although most of them still not been properly evaluated. On the valuation procedures in the companies interviewed concluded that these processes do not use these mainly for lack of knowledge and non-mandatory standard, in addition to the risks involved disclose such information companies.